Staphylococcus aureus Nasal Colonization in Spanish Children. The COSACO Nationwide Surveillance Study - del Rosal T; Méndez-Echevarría A; Garcia-Vera C; Escosa-Garcia L; Agud M; Chaves F; Román F; Gutierrez-Fernandez J; Ruiz de Gopegui E; Ruiz-Carrascoso G; Ruiz-Gallego MC; Bernet A; et al. (Infection and Drug Resistance, 2020)
Teresa del Rosal,1,2 Ana Méndez-Echevarría,1,2 Cesar Garcia-Vera,3 Luis Escosa-Garcia,1,2 Martin Agud,1 Fernando Chaves,4 Federico Román,5 José Gutierrez-Fernandez,6 Enrique Ruiz de Gopegui,7 Guillermo Ruiz-Carrascoso,8 Maria del Carmen Ruiz-Gallego,9 Albert Bernet,10 Sara Maria Quevedo,11 Ana Maria Fernández-Verdugo,12 Jesús Díez-Sebastian,13 Cristina Calvo1,2 On behalf of the COSACO Study Group1Pediatric Infectious and Tropical Diseases Department, Hospital Universitario La Paz, Madrid, Spain; 2Translational Research Network in Pediatric Infectious Diseases (RITIP), Institute for Health Research IdiPAZ, Madrid, Spain; 3“José Ramón Muñoz Fernández” Health Care Center, Aragón Health Service, Zaragoza, Spain; 4Department of Clinical Microbiology, Hospital Universitario 12 de Octubre, Madrid, Spain; 5Laboratory of Nosocomial Infections, Department of Bacteriology, CNM, Instituto de Salud Carlos III, Madrid, Spain; 6Department of Microbiology, Hospital Virgen de las Nieves, Granada, Spain; 7Department of Clinical Microbiology, Hospital Universitari Son Espases. Servicio de Microbiología, Palma de Mallorca, Spain; 8Department of Clinical Microbiology, Hospital Universitario La Paz, Madrid, Spain; 9Department of Microbiology, Hospital Universitario Virgen del Rocío, Sevilla, Spain; 10Section of Microbiology, Arnau de Vilanova University Hospital, Lleida, Spain; 11Department of Microbiology, Hospital Universitario Severo Ochoa, Leganes, Spain; 12Department of Microbiology, Hospital Universitario Central de Asturias, Oviedo, Spain; 13Department of Preventive Medicine, Hospital Universitario La Paz, Madrid, SpainCorrespondence: Ana Méndez-Echevarría Pediatric Infectious and Tropical Diseases Department. Hospital La Paz-IdiPAZ, Paseo de la Castellana 261, Madrid 28046, SpainTel/Fax +34-917277479Email amendezes@yahoo.esObjective: To assess the prevalence and risk factors for S. aureus and methicillin-resistant S. aureus (MRSA) nasal colonization in Spanish children.Methods: Cross-sectional study of patients < 14 years from primary care centers all over Spain. Clinical data and nasal aspirates were collected from March to July 2018.Results: A total of 1876 patients were enrolled. Prevalence of S. aureus and MRSA colonization were 33% (95% CI 30.9– 35.1) and 1.44% (95% CI 0.9– 2), respectively. Thirty-three percent of the children (633/1876) presented chronic conditions, mainly atopic dermatitis, asthma and/or allergy (524/633). Factors associated with S. aureus colonization were age ≥ 5 years (OR 1.10, 95% CI 1.07– 1.12), male sex (OR 1.43, 95% CI 1.17– 1.76), urban setting (OR 1.46, 95% CI 1.08– 1.97) and the presence of asthma, atopic dermatitis or allergies (OR 1.25; 95% CI: 1.093– 1.43). Rural residence was the only factor associated with MRSA colonization (OR 3.62, 95% CI 1.57– 8.36). MRSA was more frequently resistant than methicillin-susceptible S. aureus to ciprofloxacin [41.2% vs 2.6%; p< 0.0001], clindamycin [26% vs 16.9%; p=0.39], and mupirocin [14.3% vs 6.7%; p=0.18]. None of the MRSA strains was resistant to tetracycline, fosfomycin, vancomycin or daptomycin.Conclusions: The main risk factors for S. aureus colonization in Spanish children are being above five years of age, male gender, atopic dermatitis, asthma or allergy, and residence in urban areas. MRSA colonization is low, but higher than in other European countries and is associated with rural settings.Keywords: S. aureus, MRSA, child, colonization